2019
DOI: 10.1038/s42255-019-0044-9
|View full text |Cite|
|
Sign up to set email alerts
|

Liver macrophages regulate systemic metabolism through non-inflammatory factors

Abstract: Liver macrophages (LMs) have been proposed to contribute to metabolic disease through secretion of inflammatory cytokines. However, anti-inflammatory drugs lead to only modest improvements in systemic metabolism. Here we show that LMs do not undergo a proinflammatory phenotypic switch in obesity-induced insulin resistance in flies, mice and humans. Instead, we find that LMs produce non-inflammatory factors, such as insulin-like growth factor-binding protein 7 (IGFBP7), that directly regulate liver metabolism. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
67
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 82 publications
(75 citation statements)
references
References 72 publications
7
67
0
1
Order By: Relevance
“…Surprisingly, unbiased transcriptomic analysis revealed no differences in terms of expression of genes associated with a pro-inflammatory signature, between liver macrophages from lean and obese patients (similar data were obtained from mice fed an HFD for 9 weeks). Metabolic impairments are not associated with a pro-inflammatory activation of liver macrophages (78). However, the transcriptomic inflammatory signature is indeed variant between the stages of benign steatosis and NASH.…”
Section: Liver Macrophages In Metabolic Inflammationmentioning
confidence: 91%
“…Surprisingly, unbiased transcriptomic analysis revealed no differences in terms of expression of genes associated with a pro-inflammatory signature, between liver macrophages from lean and obese patients (similar data were obtained from mice fed an HFD for 9 weeks). Metabolic impairments are not associated with a pro-inflammatory activation of liver macrophages (78). However, the transcriptomic inflammatory signature is indeed variant between the stages of benign steatosis and NASH.…”
Section: Liver Macrophages In Metabolic Inflammationmentioning
confidence: 91%
“…PHH spheroids were also recently used to interrogate the protective role of nitrite in reducing chemically and metabolically induced steatosis . Moreover, spheroid cultures were used to reveal the critical role of insulin‐like growth factor binding protein 7, a factor secreted by liver macrophages that binds to the hepatocyte insulin receptor and induces lipogenesis and gluconeogenesis, thus revealing how macrophages contribute to insulin resistance independent of inflammation …”
Section: Applications Of Advanced Primary Human Hepatocyte Culture Momentioning
confidence: 99%
“…We have also demonstrated that, during obesity, LMs produce non-inflammatory factors able to regulate insulin sensitivity but nonetheless display signs of oxidative stress. Indeed, transcriptomic profiling showed that several metabolic pathways involved in ROS/RNS production such as the tricarboxylic acid cycle (TCA) cycle and oxidative phosphorylation (OXPHOS) were dysregulated in the LMs of obese compared to control mice (10). We therefore hypothesized that LMs may regulate oxidative stress independently of their inflammatory status in obesity-induced insulin resistance.…”
Section: Introductionmentioning
confidence: 99%